MERANCANG ROUTER INTERNET MENGGUNAKAN SISTEM OPERASI UBUNTU - Bersama Sinuraya; Peristiwa Ketaren (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2017)
The internet is and the most important source for obtaining information. Internet is closely associated with the world of education. To meet and such facilities, it i s necessary to build a network router connected to the Internet network. The network is expected to be used for means of learning in particular education. This router network construction to continue functioning for a signal from the computer to another computer, as well as security tools such as firewalls are implemented through a router.